World Food Day 2015: Siboniso Moyo on the importance of livestock insurance for dry areas - Moyo, Siboniso (International Livestock Research Institute, 2015)
Periscope interview with Siboniso Moyo, program leader of the the ILRI Animal Science for Sustainable Productivity program and director general's representative in Ethiopia. Filmed for World Food Day 2015.